INNOVATIVE POTENTIAL OF NUCLEAR ENERGY - Е. Kamchatova (Вестник университета, 2017)
This article examines the role of nuclear energy and the main problems of its development: economic, political, technological and human resources. Analysis of the nuclear power develop-ment Strategy up to 2030 are presented from a position of in-novative approach in the selection of priority areas such as power generation increase in nuclear power plants, the for-mation and development of the main power equipment engi-neering, nuclear fuel cycle, resource development and produc-tion base. An analysis of the investment program of JSC «Ros-energoatom Concern» is presented.